Desempenho da estimulação elétrica nervosa transcutânea versus laserterapia de baixa intensidade no alívio da dor e melhora da função na osteoartrite de joelho: protocolo de revisão sistemática - Cordeiro, Samir Emanuel Mesquita (Brasil, 2022)
Osteoarthritis is a clinical condition characterized by the deterioration of synovial cartilage, and affects mainly weight-bearing joints due to the mechanical stress to which they are subjected, with the knee being the most affected. This protocol aims to outline the objectives and procedures for a systematic review in order to compare the effectiveness of these two treatment strategies in relation to pain and functional capacity of the knee with osteoarthritis, through a bibliographic survey with searches in five electronic databases. Randomized controlled clinical trials published in the last ten years, with a score of 6 on the PEDro scale, without restriction on the age or sex of the participants, and that compared TENS and LLLT with other therapeutic modalities or placebo will be included. A pilot screening will be carried out, with the selection of articles and data analysis being performed by two independent reviewers. The risk of bias will be assessed using the PEDro scale. Information will be compiled through random effects meta-analysis for corresponding results across methodological, clinical and statistical characteristics, with a narrative synthesis for each outcome being made if this is not possible. The articles selected in the pilot screening have an average score of 7.6 on the PEDro scale and provide evidence that supports the effectiveness of TENS and LLLT in knee osteoarthritis. It is expected that the results obtained in this study lead to a better direction of physical therapy clinical practice, optimizing treatment and producing better results in the management of KOA.